Уголовный процесс: учебник / под редакцией А. С. Кобликова - Кобликов А.С. (Норма, 2000)
Экземпляры: Аб (20160923) / Инвентарный номер: 36990 / Цена: 54.00 / Авт.знак: У26 / ГРНТИ: 10.79 / ББК: 67.411